Plant growth promoting microorganisms (PGPM) as an eco-friendly option to mitigate water deficit in soybean (Glycine max L.) Growth, physio-biochemical properties and oil content - Yaghoubian, Iraj (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.